KONTRIBUSI INDUSTRIALISASI DI DESA PADA KEHIDUPAN MASYARAKAT PEDESAAN - Tantan Hermansah; Risna Siti Rahmah (Program Studi Pengembangan Masyarakat Islam (PMI) FIDIKOM, UIN Syarif Hidayatullah Jakarta, 2020)
AbstractRice is the most important food source and the government is obliged to realize its availability and fulfillment. This study aims to: (1) analyze the level of farmer participation in increasing rice production; and (2) analyzing factors that influence the level of farmers' participation in increasing rice production. This study used a survey method and was conducted in March to May 2017 in Tabir District, Merangin Regency, Jambi Province. The number of samples of this study was 92 people. The analytical method used is descriptive statistics and inferential statistics (Path Analysis) which are equipped with qualitative data. The results of the study show that: (1) The level of participation of farmers in increasing rice production is quite good, meaning that farmers have sufficiently participated in efforts to increase rice production through the Upsus Pajale program; and (2) Factors that directly influence the level of farmer participation in increasing rice production are the intensity of interaction between farmers and extension workers, the level of knowledge of farmers about the role of extension workers, the number of family dependents, involvement in farmer groups, and length of farming.Keywords: participation; farmers; increased rice productionAbstrakPadi merupakan sumber pangan paling utama dan pemerintah berkewajiban mewujudkan ketersediaan serta pemenuhannya. Penelitian ini bertujuan untuk: (1) menganalisis tingkat partisipasi petani dalam peningkatan produksi padi; dan (2) menganalisis faktor-faktor yang mempengaruhi tingkat partisipasi petani dalam peningkatan produksi padi. Penelitian ini menggunakan metode survei dan dilaksanakan pada bulan Maret hingga Mei 2017 di KecamatanTabir Kabupaten Merangin Provinsi Jambi. Jumlah sampel penelitian ini adalah 92 orang. Metode analisis yang digunakan adalah statistik deskriptif dan statistik inferensial (Path Analysis) yang dilengkapi dengan data kualitatif. Hasil penelitian menunjukkan bahwa: (1) Tingkat partisipasi petani dalam peningkatan produksi padi cukup baik, berarti petani sudah cukup ikut serta dalam upaya peningkatan produksi padi melalui program Upsus Pajale; dan (2) Faktor yang berpengaruh secara langsung terhadap tingkat partisipasi petani dalam peningkatan produksi padi adalah intensitas interaksi petani dengan penyuluh, tingkat pengetahuan petani tentang peranan penyuluh, jumlah tanggungan keluarga, keterlibatan dalam kelompoktani, dan lama berusahatani.Kata kunci: partisipasi; petani; peningkatan produksi padi